Manajemen Akhir Hayat Pasien Sakit Kritis Di ICU COVID-19 - Adiyanto, Bowo; Widodo, Untung; Hernawan, Agung Diky (Jurnal Komplikasi Anestesi, 2021)
End-of-life condition was showed with symptoms of brain-stem death and functional impairment of breathing effort that persisted at fifth day of care. Physician explained to patient’s family about end-of-life condition, prognose, probability, and a desicion making that would had to make. Family decided to accept this condition, wish to continue medication but not to resuscitate if patient’s condition became worst. A chaplain gave spiritual care, end-of-life counceling, and praying to patient. Unfortunately, there was no intensive communication among medical teams about end-of-life condition. Patient care was underwent until the time of death with permitted family at patient’s bedside, not gave cardiopulmonal resuscitation as family’s wishes and pronaounced death in front of family.